Screening for primary immunodeficiency diseases by next‐generation sequencing in early life - Sun, Jinqiao (Clin Transl Immunology, 2020)
OBJECTIVE: We aimed to use next‐generation sequencing (NGS) for the early diagnosis of primary immunodeficiency diseases (PIDs) and define its effects on medical management for an infant cohort in early life. METHODS: A single‐centre study was conducted from November 2015 to April 2018. Infants less than 3 months old with infections or abnormal white blood cell counts were enrolled in the study. Gene variants were analysed by NGS, and once a mutation was found in a PID‐associated gene, the immune functions associated with this mutation were detected. The diagnosis rate of PIDs in the cohort was the main outcome. The patients received corresponding management and follow‐up treatments. RESULTS: Among 2392 patients who were genetically tested with NGS, 51 infants were diagnosed with PIDs. Seven types of PIDs were detected, and the most common (25/51, 49%) were combined immunodeficiencies with associated or syndromic features. Thirty‐five patients (68.6%) were cured or had improved outcomes after being diagnosed with PID. The NGS cost was US$280 per case. CONCLUSIONS: This study not only highlighted the potential of NGS to rapidly deliver molecular diagnoses of PIDs but also indicated that the prevalence of PIDs is underestimated. With broader use, this approach has the potential to alter clinical strategies.